Liquefied natural gas as marine bunker : feasibility and future prospects - Kok, Lionel Fook Yuen (2018)
By 1st January 2020, IMO’s global sulphur cap regulation would have taken effect, leading to a reduction in the current sulphur emission limit from 3.50% m/m to 0.5% m/m. Furthermore, the International Maritime Organization has explicitly stated and reaffirmed that there will be no extension given nor a phased transition for implementation. As a result, to comply with the regulations, shipowners are pressed for time into considering the various options available to them. Currently, the usage of LNG as a marine fuel, presents itself as one of the most attractive and future-proof solution, due to it having the cleanest emission when compared with other alternatives. However, this option faces a problem and a commonly heard phrase known as the “Chicken and Egg” conundrum; in which neither the shipowners nor LNG bunker suppliers are willing to commit in making the first move due to the large investment uncertainty and the incurrence of the associated capital-intensive expenditure. Consequently, this is where government intervention should step in, by providing support to break this dilemma cycle, and accelerate the adoption of LNG as a marine fuel. Hence, understanding the important role that government plays, the objective of this paper is to analyze the various government regulations and policies that promote the adoption of LNG as a preferred marine fuel alternative through a multi-case study approach. With this in mind, a proposed framework will then be developed based on learning from the success and effectiveness of these policies implemented in other countries.